2020
DOI: 10.1038/s41467-020-19326-3
|View full text |Cite
|
Sign up to set email alerts
|

Extensive 5′-surveillance guards against non-canonical NAD-caps of nuclear mRNAs in yeast

Abstract: The ubiquitous redox coenzyme nicotinamide adenine dinucleotide (NAD) acts as a non-canonical cap structure on prokaryotic and eukaryotic ribonucleic acids. Here we find that in budding yeast, NAD-RNAs are abundant (>1400 species), short (<170 nt), and mostly correspond to mRNA 5′-ends. The modification percentage of transcripts is low (<5%). NAD incorporation occurs mainly during transcription initiation by RNA polymerase II, which uses distinct promoters with a YAAG core motif for this purpose. Most… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 56 publications
0
44
2
Order By: Relevance
“…SPAAC tagging resulted in much longer reads and a much higher efficiency in identifying NAD-RNAs than CuAAC tagging. In budding yeast, it was recently reported that most NAD-mRNAs identified using NAD captureSeq were 5′ fragments from thousands of genes, which might be incidentally produced ( 21 ). NAD-mRNAs identified from E. coli using NAD captureSeq also showed enrichment in 5′ fragments ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SPAAC tagging resulted in much longer reads and a much higher efficiency in identifying NAD-RNAs than CuAAC tagging. In budding yeast, it was recently reported that most NAD-mRNAs identified using NAD captureSeq were 5′ fragments from thousands of genes, which might be incidentally produced ( 21 ). NAD-mRNAs identified from E. coli using NAD captureSeq also showed enrichment in 5′ fragments ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…A large majority of NAD-RNAs of the high-confidence NAD-RNAs identified in this study are from protein-coding genes, but some genes coding for small regulatory RNAs produced a high proportion of their transcripts as NAD-RNAs. NAD-RNAs from Bacillus subtilis , yeast, mammals, and Arabidopsis were also found to be mainly from protein-coding genes ( 10 , 11 , 13 , 14 , 34 ). It has been reported that in vitro-synthesized NAD-mRNAs were not translated in a yeast extract or in mammalian cells ( 11 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An adaptation of the aforementioned protocol also led to the detection of NAD-capped RNA sequences in Gram-positive bacteria, such as Bacillus subtilis and Staphylococcus aureus [ 20 , 21 ], as well as in eukaryotes, like Saccharomyces cerevisiae , Arabidopsis thaliana and Homo sapiens [ 22 , 23 , 24 , 25 ]. In addition, the existence of enzymes that specifically target 5′-NAD-, dephospho-CoA- or FAD-capped RNAs, such as the nudix hydrolase NudC and proteins of the DXO family, supports the idea of regulated capping and decapping processes [ 24 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%